Macro to micro phase separation of chiral active swimmers - Semwal V.; Joshi J.; Dikshit S.; Mishra S. (My University, 2025)
Chirality is naturally present in many microswimmers. It can significantly affect their individual and collective behavior. We perform a detailed study of a collection of chiral active swimmers interacting through soft repulsion on a two-dimensional substrate. We observe that chirality considerably affects the steady-state properties of the system. On varying the chirality and activity of particles, three distinct phases are observed. For small chirality, when activity is dominant, particles show enhanced dynamics, and motility drives the formation of macroscopic ordered clusters. For large chirality, localized dynamics give rise to a homogeneous phase. When chirality and activity are comparable, an intermediate micro-clustered phase is observed. Our study gives a detailed insight into the effect of chirality on the properties of a collection of chiral active particles, which can be useful for understanding the dynamics and steady state of many natural microswimmers. © 2023